Metrology in electricity and magnetism: EURAMET activities today and tomorrow. (4th August 2017) - Piquemal, F; Jeckelmann, B; Callegaro, L; Hällström, J; Janssen, T J B M; Melcher, J; Rietveld, G; Siegner, U; Wright, P; Zeier, M
Abstract: Metrology dedicated to electricity and magnetism has changed considerably in recent years. It encompasses almost all modern scientific, industrial, and societal challenges, e.g. the revision of the International System of Units, the profound transformation of industry, changes in energy use and generation, health, and environment, as well as nanotechnologies (including graphene and 2D materials) and quantum engineering. Over the same period, driven by the globalization of worldwide trade, the Mutual Recognition Arrangement (referred to as the CIPM MRA) was set up. As a result, the regional metrology organizations (RMOs) of national metrology institutes have grown in significance. EURAMET is the European RMO and has been very prominent in developing a strategic research agenda (SRA) and has established a comprehensive research programme. This paper reviews the highlights of EURAMET in electrical metrology within the European Metrology Research Programme and its main contributions to the CIPM MRA. In 2012 EURAMET undertook an extensive roadmapping exercise for proposed activities for the next decade which will also be discussed in this paper. This work has resulted in a new SRA of the second largest European funding programme: European Metrology Programme for Innovation and Research.